Harvest and water management by small cattle farmers in Caquetá, Colombia - Alliance of Bioversity International and CIAT (Bioversity International and the International Center for Tropical Agriculture, 2022)
Livestock production is the main source of income for thousands of rural families. Extreme climate events such as drought have a strong impact on their livelihoods.